2013
DOI: 10.1021/jp400829z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of the Effect of the Inductive-to-Capacitive Transition in Propanethiol Plasma Polymer Chemistry

Abstract: The influence of the capacitive (E)-to-inductive transition (H) in inductively coupled plasma discharges is investigated for propanethiol plasma polymerization. In the E mode, at low plasma density, the sulfur content in the layers, measured by XPS, is quite high and strongly decreases after aging in the air. This phenomenon is attributed to the desorption of trapped sulfur-based molecules (e.g., H 2 S). In the H mode, presumably higher surface temperature prevents the trapping scenario during the layer growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 47 publications
8
69
0
Order By: Relevance
“…The most intense peaks detected result from fragments having from one to three carbons. THIRY et al [17] also found the same behavior on RGA analysis, with most carbonaceous compounds with 1-3 carbons. The higher molar mass fragments need more energetic sources to be produced, or more temperature to become volatile in the vacuum chamber.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The most intense peaks detected result from fragments having from one to three carbons. THIRY et al [17] also found the same behavior on RGA analysis, with most carbonaceous compounds with 1-3 carbons. The higher molar mass fragments need more energetic sources to be produced, or more temperature to become volatile in the vacuum chamber.…”
Section: Resultsmentioning
confidence: 58%
“…THIRY et al [17] studied different treatment behaviours of propanethiol (in gas phase) to material deposition and growth, in both ICP discharges modes. The results showed that higher discharge temperatures and electron densities leaded to higher fragmentation of propanethiol.…”
Section: Introductionmentioning
confidence: 99%
“…However, the possible production of CS 2 molecules having the same mass than the precursor may lead to a wrong interpretation of the data. [19] Nevertheless, due to the relative abundance of the isotope 34 S ($4%), both molecules can be discriminated by examining their isotropic distribution through the evaluation of the I (m/z ¼ 78)/I (m/z ¼ 76) ratio. [38] Its evolution as a function of hPi is depicted in Figure S2, Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…[3,17] In this context, we have recently published a detailed study on the influence of the experimental parameters on the chemical properties of propanethiol plasma polymer (Pr-PPF) synthesized in RF discharges. [18,19] One of the main conclusion of this work is that, depending on the growth conditions (capacitive or inductive coupling of the discharge, power, pressure,. .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation